Educational implications of 'six thinking hats' - Bosanac Maja M.; Grandić Radovan B. (University of Kragujevac - Faculty of Pedagogy, Užice, 2020)
Modern education is increasingly linked to market principles. On the one hand, proponents of this approach emphasize the need to develop an entrepreneurial mindset, while critics point out that this approach neglects the humanistic dimension of education. The goal of the paper is to set up a "six thinking hats" learning model as a way to encourage the development of creative thinking. Although its primary use is in non-formal education (creative training and interactive workshops), this model also has its application within the academic community. Within formal education, the authors advocate the possibility to widespread the application of this model, technique, or role-playing game as it is called by different authors, which points to the pluralism of approaches. Also, the analysis of the studied literature revealed the application of the model at different levels of education. In conclusion, it is stated that although it is not a conventional and widely accepted model, it can be a good way to foster creative and entrepreneurial thinking. The application of this model is recommended for teachers who find the traditional approach to teaching rigid and who are ready for changes that involve a more active pupil/student role.